Simultaneous treatment of parapelvic renal cysts and stones by flexible ureterorenoscopy with a novel four-step cyst localization strategy - Ning Kang; Xing Guan; Liming Song; Xiaodong Zhang; Junhui Zhang (International Brazilian Journal of Urology)
ABSTRACT Objective: To assess the safety, feasibility, and efficacy of simultaneous treatment of parapelvic renal cysts and stones by flexible ureterorenoscopy with a novel four-step cyst localization strategy in selected patients. Patients and Methods: We retrospectively reviewed 11 consecutive cases of parapelvic renal cysts with concomitant calculi treated by flexible ureterorenoscopy and laser lithotripsy (FURSL). Marsupialization was performed subsequently with holmium: YAG laser in our institution. Fragmentation was used to manage renal stones and a novel four-step cyst localization strategy was applied in each case for marsupialization. Results: There were no intraoperative complications. Two cases of cystitis were reported postoperatively. The mean operative times of FURSL and marsupialization were 23.6 ± 3.9 minutes and 29.1 ± 9.7 minutes, respectively. During marsupialization, seven patients underwent the first two steps of the new strategy, two patients underwent three steps and two patients underwent all four steps. The mean reduction in hemoglobin level was 4.7 ± 1.7 g / L (range 3-8 g / L). The mean length of hospital stay was 1.2 ± 0.4 days. During a mean follow-up duration of 18 months, all cases remained stone-free and there was no stone recurrence. Parapelvic cysts became undetectable in eight cases and decreased in size by at least half in three cases. Conclusion: With appropriate patient selection, FURSL and marsupialization with a four-step cyst localization strategy is feasible, safe, and effective in treating parapelvic renal cysts with concomitant calculi.